SEMANTIC-PRAGMATIC ANALYSIS OF COLLOCATIONS IN UZBEK AND ENGLISH: TRANSLATION CHALLENGES - Adxamova Shirin Farxodjon qizi (Bright Mind Publishing, 2025)
This study examines the semantic-pragmatic characteristics of collocations in Uzbek and English languages, focusing on the challenges encountered in translation processes. Collocations represent a fundamental aspect of natural language usage, yet their translation presents significant difficulties due to cross-linguistic variations in lexical combinations, cultural connotations, and pragmatic functions.
Keywords: Collocations, semantic-pragmatic analysis, translation challenges, cross-linguistic comparison, lexical patterns, cultural linguistics.